2016
DOI: 10.3399/bjgp16x683821
|View full text |Cite
|
Sign up to set email alerts
|

Primary care clinician antibiotic prescribing decisions in consultations for children with RTIs: a qualitative interview study

Abstract: BackgroundRespiratory tract infections (RTIs) are a major primary care challenge in children because they are common and costly, there is uncertainty regarding their diagnosis, prognosis, and management, and the overuse of antibiotics leads to illness medicalisation and bacterial resistance.AimTo investigate healthcare professional (HCP) diagnostic and antibiotic prescribing decisions for children with RTIs.Design and settingSemi-structured interviews conducted with 22 GPs and six nurses. HCPs were recruited f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
113
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(121 citation statements)
references
References 33 publications
5
113
1
2
Order By: Relevance
“…Primary care clinicians acknowledge that they prescribe antibiotics for a range of medical and non-medical reasons, 10 particularly in children, who are seen as vulnerable 11 and whose clinical state can change rapidly. Many clinicians report that they prescribe antibiotics just in case, 12 to mitigate perceived risk of future hospital admission and complications,13, 14 and that failing to provide a prescription for a child who subsequently becomes seriously unwell is professionally unacceptable 11 . If primary care clinicians could identify children at low (or very low) risk of such future complications, the reduced clinical uncertainty could lead to a reduced use of antibiotics in these groups of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Primary care clinicians acknowledge that they prescribe antibiotics for a range of medical and non-medical reasons, 10 particularly in children, who are seen as vulnerable 11 and whose clinical state can change rapidly. Many clinicians report that they prescribe antibiotics just in case, 12 to mitigate perceived risk of future hospital admission and complications,13, 14 and that failing to provide a prescription for a child who subsequently becomes seriously unwell is professionally unacceptable 11 . If primary care clinicians could identify children at low (or very low) risk of such future complications, the reduced clinical uncertainty could lead to a reduced use of antibiotics in these groups of patients.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Common harms and the contribution to antibiotic resistance, 9 now a global public health crisis, 10,11 are rarely addressed. Primary care clinicians resort to antibiotics for many reasons, including diagnostic uncertainty 12,13 ; a desire to provide an unwell child with something to help 13,14 ; and an attempt to reduce visit length 12,13 and achieve parental satisfaction. 15 Interacting with many of these reasons is parental pressure for antibiotics, both articulated and perceived by clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…In the studies of high income countries (HICs), the high workload and limited time have been identified as factors that influenced providers' antibiotic-related behavior for children in primary care [57,58]. These factors were also noted by providers in our study; however, they appeared to combine in different ways among providers working in different parts of China's healthcare system, pointing to the interactions between different healthcare institutions.…”
Section: Discussionmentioning
confidence: 41%